The reluctant judge. About the art of (no) judging in “The Merchant of Venice” - Velo Dalbrenta, Daniele (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
In the literary classification, Shakespeare’s The Merchant of Venice should be formally considered a comedy, but it could be barely considered such a kind of work. In fact, at the center of the scene, there is the tragedy of Shylock, the controversial Jewish character whose ‘strange’ legal (?) request of an equal pound of Antonio’s flesh supports the plot. Defeated by the formalistic argument used in the crucial trial, Shylock doesn’t obtain what he claimed, and he loses almost all, except for his life. However, the legal argument used in the trial doesn’t come from the Duke, who should be the ‘real’ judge, but from Portia, a disguised character who has reason to oppose the despised Jew. So, who is who in this ‘comedy’, and, above all (for the jurists), who is the judge? Perhaps, by rereading The Merchant of Venice, we could learn more about the jurisdictional function than studying the (formal) jurisprudence. Keywords: Judicial System; Judgement; Juridical Argumentation; Judicial Reasoning; Juridical Formalism Indice: 1. Duplicità nascoste – 2. Giustizia o mercimonio? – 2.1 The Jaw shall have alla justice – 2.2 Is that the law? – 2.3 Thou shalt have nothing but the forfeiture – 3. Il giudice che non c’è